1973
DOI: 10.3181/00379727-143-37253
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of High-Fat Diets on Estrous Cycles, Sperm Production and Fertility of Rats

Abstract: Numerous studies have related nutrition to reproduction (1-4), but only a few dealt with the effect of high-fat diets on reproduction and these were confined to the requirement of essential fatty acids for reproductive performance. Deuel et al. (5) and Sheer et al. (6) reported that rats fed diets containing high levels of fat had more rapid growth and more efficient reproductive and lactational performances than rats fed diets containing low concentrations of fats. However, French et al. ( 7 ) found decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Earlier studies suggested that fat-derived signals (e.g., fatty acids and estrogen) (11,29,30) could link adiposity and reproduction, while Wade et al (31) have proposed instead that glucose is the metabolic signal involved in the central regulation of reproduction. Since concentrations of the fat-derived hormone, leptin, correlate with adipose tissue mass in the fed state (16-18) and leptin levels fall with starvation (17,19), leptin could provide the relevant information to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies suggested that fat-derived signals (e.g., fatty acids and estrogen) (11,29,30) could link adiposity and reproduction, while Wade et al (31) have proposed instead that glucose is the metabolic signal involved in the central regulation of reproduction. Since concentrations of the fat-derived hormone, leptin, correlate with adipose tissue mass in the fed state (16-18) and leptin levels fall with starvation (17,19), leptin could provide the relevant information to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Weight growth in the rat has been reported to be more rapid on high-fat diets than on normal or low-fat diets (3)(4)(5). Female rats on high-fat diets, therefore, should have vaginal opening and estrus earlier than on a low-fat diet.…”
mentioning
confidence: 99%
“…Diet, food and water consumption and body weight gains per se can also have an important influence on many aspects of animal responses, including shifts in metabolic, hormonal and homeostatic mechanisms (Kennedy, 1969), disease processes (Berg & Simms, 1960;Paynter, 1984;Ross & Bras, 1965;Tannenbaum, 1940;Cohen et al, 1994) and maturation (Innami et al, 1973). (See also Subsection 1.2.2.)…”
Section: Body Weight Changes and Food And Water Consumptionmentioning
confidence: 99%